1999
DOI: 10.1054/jhsb.1998.0180
|View full text |Cite
|
Sign up to set email alerts
|

Time Off Work After Occupational Hand Injuries

Abstract: This study analysed the impact of several factors on the start and duration of time off work among 802 patients with occupational hand injuries, in order to identify prognostic indicators. The study showed that external factors such as work and social condition seemed to have less influence on time off work than expected, whereas advice from doctors, flashbacks and impairment symptoms were important determinants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 6 publications
2
36
1
1
Order By: Relevance
“…It is well known from clinical experience and previous studies that injuries to bones and joints as well as injuries to tendons and nerves are significant indicators for being off work and having a prolonged time off work [14]. It is also generally recognised that hand injuries of manual workers result in longer time off work than of other members of the working population [15].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known from clinical experience and previous studies that injuries to bones and joints as well as injuries to tendons and nerves are significant indicators for being off work and having a prolonged time off work [14]. It is also generally recognised that hand injuries of manual workers result in longer time off work than of other members of the working population [15].…”
Section: Discussionmentioning
confidence: 99%
“…The patients are diagnosed according to the ICD10 code system. Data validation has been performed continuously since the formation of the register 12 16 17. From 2003–2010, a total of 33 030 work-related injuries were registered in the ED, representing 26 129 persons with one or more visits in the period.…”
Section: Methodsmentioning
confidence: 99%
“…Manual laborers reported difficulties in performing their work as a result of the decrease in hand strength. A former study confirmed this association, showing that manual laborers had a longer period of absenteeism and subsequent difficulty in returning to the workplace 28 . The multivariate analysis showed that greater worker satisfaction in relation to occupational performance was associated with the RTW.…”
Section: Discussionmentioning
confidence: 75%